Ensayo comparativo de rendimiento y resistencia a enfermedades más comunes en 13 Líneas y 4 Variedades de Arroz (Oryza sativa L.) bajo riego en el distrito de Juan Guerra. - Arévalo Fasanando, María Elena (1997)
In order to evalue the grain yields and quality and other agronomic characteristics desirables of the best rice lines, it was carried out experiment in a clay soil in the “Porvenir” Experimental Station, located in the Bajo Mayo Valley. Belonging to Province and Region San Martin ( Perú). The geagraphical location is at 6° 26' west longitud and 6º34' south to Greanwich latitud and 356 m. above sea level it was used a complete blocks randomized design, with four repetitions. The best treatments were obtained with T11 (6661.5 K/hal; T12(6259 . 75 Kg/h.), and T14 (6259.75 kg/ha); and T6 (4627.75 Kg/ha) there isn’t significant differences between blocks but highly significant differences between treatments, probably due to the morphology characteristics of the plant. Respect to cost – benefit, it was expressed in percentage the treatment T11, it was the most economic one with 72.08 % and the treatment T6, the most uneconomic with 100.12%. It was concluded that the best treatment is T11 with a yield of 6661.5 Kg/ha; a qrinding quality of 70 % entire grains and 7 5 break grains; 189 .971 full grains per spike and 29.75 g of wigh in 1000 grains; exceeding a the treatments T1 ; T7; to and at the witness treatment.